INOVASI PELAYANAN TRANSPORTASI PUBLIK SUROBOYO BUS RAPID TRANSIT RUTE UTARA - SELATAN - Sela Febrina (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2021)
Improving the service quality is required to fulfill the community necessities for secure mass transportation, and to acquire comfortable, safe, and affordable services. Through public transportation innovation in Bus Rapid Transit (BRT), Suroboyo Bus is expected to be able to motivate the public enthusiasm to change over the use of public transportation services. It is also expected to increase public satisfaction toward the services in mass transportation. Furthermore, the study aims to figure out how the innovation of public transportation service in BRT (Bus Rapid Transit) which is called as Suroboyo Bus with north to south route. This is qualitative descriptive study using interview, documentation, and observation analysis in the data collection techniques. The study uses the theory of transportation service innovation from Rogers in Yogi Suwarno (2008). The results indicate the innovation of public transportation services that have been implemented by the Surabaya government in collaboration with the Transportation Office and Sanitary and Open Space Cleanliness Office. This program has been conducted well, however, it requires some improvements because it has lack of bus stops resulting in the limitation of places that can be passed by Suroboyo Bus. Moreover, the number of Suroboyo Bus fleets should be increased.